A smart porous wood-supported flower-like NiS/Ni conjunction with vitrimer co-effect as a multifunctional material with reshaping, shape-memory, and self-healing properties for applications in high-performance supercapacitors, catalysts, and sensors. Issue 21 (20th May 2020) - Xiong, Chuanyin; Li, Bingbing; Liu, Heguang; Zhao, Wei; Duan, Chao; Wu, Haiwei; Ni, Yonghao
Abstract : Wood-based materials are attracting extensive attention for applications in energy storage due to their environmental friendliness and the presence of numerous channels in their structure. Abstract : Wood-based materials are attracting extensive attention for applications in energy storage due to their environmental friendliness and the presence of numerous channels in their structure. However, the poor conductivity and flexibility of wood restrict its application. Although some researchers have made several efforts to improve the conductivity of wood by carbonization, the wood-based materials become brittle instead of flexible. Moreover, the cycling stability of carbonized wood-based materials becomes very poor due to their falling off during the process of electrochemical energy storage. Herein, for the first time, a smart carbonized lignin-free wood (CLFW)@Ni–NiS/vitrimer(v ) composite multifunctional material with good reshaping, shape-memory, and self-healing properties was designed and fabricated. When assembled to a symmetric supercapacitor, the resultant CLFW@Ni–NiS/V hybrid showed not only the high gravimetric, areal, and volumetric energy densities of 38 W h kg −1, 687 μW h cm −2, and 58 W h L −1 and simultaneously maintained the high power densities of 56 kW kg −1, 202 mW cm −2, and 39 kW L −1, but also significantly enhanced cycling stability, respectively. In addition, CLFW@Ni–NiS/V presented good ORR and strain sensor properties. These outstanding advantages highlight the huge potential of smart wood-based materials with variable, shape-memory, and self-healing properties for applications in supercapacitors, catalysts, and sensors.